2018
DOI: 10.1063/1.5082119
|View full text |Cite
|
Sign up to set email alerts
|

Training algorithms for artificial neural network in predicting of the content of chemical elements in the upper soil layer

Abstract: Multilayer perceptron, generalized regression neural network, and hybrid model in predicting the spatial distribution of impurity in the topsoil of urbanized area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The method has similar data processes as a biological neural with nonlinear mapping structures, which consists of a set of interconnected units (neurons) [117]. The input neurons are predictors, linking to one layer of hidden neurons and finally linking to the output variables [118]. To obtain accurate prediction results, the network model is trained first by a set of observations.…”
Section: New Emerging Methods To Predict Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has similar data processes as a biological neural with nonlinear mapping structures, which consists of a set of interconnected units (neurons) [117]. The input neurons are predictors, linking to one layer of hidden neurons and finally linking to the output variables [118]. To obtain accurate prediction results, the network model is trained first by a set of observations.…”
Section: New Emerging Methods To Predict Soil Propertiesmentioning
confidence: 99%
“…ANNs outperform traditional statistics in handling large datasets even when the input data are noisy with low levels of precision due to the ability to reduce bias by evenly distributing training data across classes [119]. Various researchers have employed ANNs for efficient prediction of quantitative soil chemical and hydrological properties [118,120,121] and adequate mapping categorical soil taxonomic classes [122][123][124][125][126][127][128][129] based on DTMs and environmental variables. Zhao et al [93] also tested the feasibility of using ANNs for soil drainage classification and found an accuracy of 52% between field observations and digital classification.…”
Section: New Emerging Methods To Predict Soil Propertiesmentioning
confidence: 99%
“…Adequate training, validation, testing, and overall prediction accuracy were observed when the LM algorithm was used (Table 7 ). The LM algorithm which may be the fastest of the three training algorithms specifically works with loss functions presented in the form of a sum of squared errors (SSE) 45 , 46 . Unfortunately, LM cannot be applied to the cross-entropy error and the root mean squared error functions 46 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the LM is the recommended choice with better performance in terms of rapidity and the overfitting problem when there are a few thousand instances and a few hundred parameters for training the ANN 46 , 47 . In an unrelated study, the LM training algorithm was found to show the highest accuracy in comparison to different training algorithms in a MLP model that forecasted chemical elements distribution in the topsoil 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The weights can be adjusted iteratively on the basis of the training dataset. Including topographic information and other environmental variables, this method has been successfully applied to identify categorical characters, such as soil taxonomic classes and drainage classification [79,[86][87][88][89], and to predict quantitative variables including soil chemical and hydrological properties [90][91][92].…”
Section: Advanced Statistical Methodsmentioning
confidence: 99%